Socialization of Literacy Culture as an Effort to Improve Pancasila Values at Al-Amin Orphanage - Jamilah, Jamilah; Adelin, Fitra Surya (Indonesian Journal of Community Empowerment (IJCE), 2025)
Pancasila, as the foundation of the state, plays a crucial role in building the character and morality of the younger generation. Instilling Pancasila values through a culture of literacy can strengthen their identity, given the challenges of globalization. The training was conducted through interactive activities involving discussions, educational games, and reading literature related to Pancasila and local culture. A participatory approach was chosen to encourage children's involvement and interest. The activity began with an introduction to the basic concepts of Pancasila and continued with games that encouraged teamwork. The training results showed a significant increase in children's interest in reading and their understanding of Pancasila values. Observations during the training revealed that children were more active in discussions and participating in games that taught values such as tolerance and cooperation. For example, in games that emphasized teamwork, children demonstrated improved abilities in working together and communicating with one another. This program is expected to produce a young generation that is not only academically intelligent but also has character and integrity.